Genome-Wide Association Study of the Postprandial Triglyceride Response Yields Common Genetic Variation in LIPC (Hepatic Lipase). (August 2020) - Ibi, Dorina; Noordam, Raymond; van Klinken, Jan Bert; Li-Gao, Ruifang; de Mutsert, Renée; Trompet, Stella; Christen, Tim; Blauw, Lisanne L.; van Heemst, Diana; Mook-Kanamori, Dennis O.; Rosendaal, Frits R.; Jukema, J. Wouter; et al.
Abstract : Background: The increase in serum triglyceride (TG) concentrations in response to a meal is considered a risk factor for cardiovascular disease. We aimed to elucidate the genetics of the postprandial TG response through genome-wide association studies (GWAS). Methods: Participants of the NEO (Netherlands Epidemiology of Obesity) study (n=5630) consumed a liquid mixed meal after an overnight fast. GWAS of fasting and postprandial serum TG at 150 minutes were performed. To identify genetic variation of postprandial TG independent of fasting TG, we calculated the TG response at 150 minutes by the residuals of a nonlinear regression that predicted TG at 150 minutes as a function of fasting TG. Association analyses were adjusted for age, sex, and principal components in a linear regression model. Next, using the identified variants as determinants, we performed linear regression analyses on the residuals of the postprandial response of 149 nuclear magnetic resonance–based metabolite measures. Results: GWAS of fasting TG and postprandial serum TG at 150 minutes resulted in completely overlapping loci, replicating previous GWAS. From GWAS of the TG response, we identified rs7350789-A (allele frequency=0.36), mapping to hepatic lipase ( LIPC ), to be associated with a smaller increase in TG concentrations at 150 minutes (β=−0.11; P -value=5.1×10 −8 ). Rs7350789-A was associated with responses of 33 metabolite measures ( P -value <1.34×10 −3 ), mainly smaller increases of the TG-component in almost all HDL (high-density lipoprotein) subparticles (HDL-TG), a smaller decrease of HDL diameter and smaller increases of most components of VLDL (very low density lipoprotein) subparticles. Conclusions: GWAS of the TG response identified a variant near LIPC as a main contributor to postprandial TG metabolism independent of fasting TG concentrations, resulting in smaller increases of HDL-TG and VLDL subparticles. Abstract : Supplemental Digital Content is available in the text.